МОДЕЛЬ РОЗПОДІЛУ РЕСУРСІВ СЕНСОРНОЇ МЕРЕЖІ НА ОСНОВІ МОДИФІКОВАНОГО ГЕНЕТИЧНОГО АЛГОРИТМУ - Зайцев, Олександр Вікторович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
Model of resources distribution of sensor network on a basis of the modified genetic algorithm The mathematical model for maintenance of optimum distribution of information and computing resources among nodes of a sensor network is proposed. The problem of discrete optimisation is formulated. Updating of genetic algorithm which provides special coding for the decision of problems is offered.